Remote clinical prognosis in patients with coronary X syndrome. - Sebov, D. M. (Medicni Perspektivi, 2015)
The article analyzes data of 3234 coronary angiographies with established coronary X syndrome (CXS) in 217 cases, herewith expressed tortuosity of coronary arteries (ETCA) was found out in 148 (more than 2/3) of cases. A 5-years’ analysis of cardio-vascular events (CVE) in patients with CXS in comparison with the group of IHD patients and initial atherosclerosis of coronary arteries was made. Absence of reliable difference of developing severe cardio-vascular events (SCVE) between patients with initial atherosclerosis and CXS was proved. Risk of CVE development was significantey higher in patients withETCA,OR=4,93; 95% (0,62; 3929). Patients with CXS had higher risk of severe arrhythmias development as compared with IHD patients with initial atherosclerosis: OR=2,36 (1,01; 5,56). There was no reliable difference between lethality of any causes and number of coronary interventions in all groups.